Gilligan: a voice for nursing?. Issue 4 (December 1992) - Harbison, J
Abstract : The current reform of nursing education is resulting in major changes in the curricula of colleges of nursing. For the first time, ethical and moral issues are being seen as an important theme underpinning the entire course. The moral theorist with whose work most nurse teachers are acquainted is Kohlberg. In this paper, it is suggested that his work, and the conventions of morality which he exemplifies, may not be the most appropriate from which to address the moral issues facing the nurse. The author suggests that the work of Carol Gilligan of Harvard university is of great significance, not only for nurses involved in the teaching of ethics, but for all nurses. Gilligan's emphasis on caring and relationships accords with the common experience of the nurse, and echoes the current revival of interest within nursing in examining, and valuing, the phenomenon of caring.